Great saphenous vein aneurysm: A differential diagnosis of femoral hernia and review - de Miranda, Jocielle Santos (Int J Surg Case Rep, 2015)
INTRODUCTION: Venous aneurysms are unusual clinical entities that might be difficult to diagnose and usually appear as an asymptomatic incidental finding on physical examination or imaging study and discovered only during the surgical exploration. They are important differential diagnosis of groin and other subcutaneous mass. PRESENTATION OF CASE: We report a case of a 67-years-old woman who had a groin mass misdiagnosed as femoral hernia, which was subsequently diagnose as great saphena vein aneurysm in the intraoperative set and treated with ligature and resection. DISCUSSION: In conclusion, venous aneurysms of the superficial system are lesions that are important differential diagnosis of groin and other subcutaneous mass. CONCLUSION: Diagnosis is readily available by duplex ultrasonography; however, in most cases, the diagnosis is done only in the operative field.